Prevalence and Factors Associated with Risky Sexual Behaviors Among Sexually Active Female Adolescents in Zambia. - Sserwanja, Quraish; Mwamba, Daniel; Poon, Paul; Kim, Jean H. (Archives of Sexual Behavior, 2023)
Despite decades long commitment to women's reproductive health rights, sexually transmitted diseases and unintended pregnancies continue to be major public health concerns in sub-Saharan Africa. In order to provide an evidence base for future policy and services, this study aims to explore the prevalence and factors associated with risky sexual behaviors (RSB) among sexually active Zambian female adolescents using a nationally representative sample. Data on females, aged 15–19 (n = 3000), were obtained from the 2018 Zambia Demographic and Health Survey, an interviewer-administered, nationally representative survey that used multistage sampling. The study conducted multiple logistic regression to explore the correlates of RSB. Of the 3000 respondents, 49.7% (1490) reported ever having sexual intercourse of which 71.1% reported engaging in RSB. Among sexually active female adolescents, the following RSB percentage were reported: intercourse before age 16 (50.6%), nonuse of condoms at last intercourse (37.8%), engaging in transactional sex (6.2%), alcohol use at last intercourse (4.6%), and multiple sexual partners (1.9%). Educational attainment and household wealth showed strong inverse trends with RSB risk and there were notably large geographic differences in RSB within Zambia (22.1% in Lusaka region vs. 62.4% in Western province). The multiple logistic regression results revealed that those who were younger, unmarried, with less than secondary education, without access to Internet, and residents of Western Zambia were significantly more likely to have engaged in RSB (AOR: 1.74–7.69, p < 0.05). Given the negative health outcomes associated with RSB, Zambian adolescent health care programs may strategically target limited resources to the identified risk groups.